Left ventricular sphericity index predicts systolic dysfunction in rats with experimental aortic regurgitation - Roscani, Meliza Goi [UNESP]; Polegato, Bertha Furlan [UNESP]; Tanni Minamoto, Suzana Erico [UNESP]; Mena Lousada, Ana Paula [UNESP]; Minicucci, Marcos [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Amer Physiological Soc, 2014)
Although an increased left ventricular (LV) diastolic diameter (DD) and a decreased ejection fraction have been used as markers for the surgical replacement of an insufficient aortic valve, these signals may be observed when irreversible myocardium damage has already occurred. The aim of this study was to determine whether change in LV geometry predicts systolic dysfunction in experimental aortic regurgitation. Male Wistar rats underwent surgical acute aorta regurgitation (aorta regurgitation group; n = 23) or a sham operation (sham group; n = 12). After the procedure, serial transthoracic echocardiograms were performed at 1, 4, 8, and 16 wk. At the end of protocol, the LV, lungs, and liver were dissected and weighed. During the follow-up, no animal developed overt heart failure. There was a correlation between the LV sphericity index and reduced fractional shortening (P < 0.001) over time. A multiple regression model showed that the LVDD-sphericity index association at 8 wk was a better predictor of decreased fractional shortening at week 16 (R-2 = 0.50; P < 0.001) than was the LVDD alone (R-2 = 0.39; P = 0.001). LV geometry associated with increased LVDD improved the prediction of systolic dysfunction in experimental aortic regurgitation.
Keywords: heart failure; echocardiogram; eccentric hypertrophy; volume overload; valve disease